SYNTACTIC STRUCTURE OF COMPLEX SENTENCES IN RUSSIAN AND UZBEK LANGUAGES - Teshaboyeva Nargiza Makhammadovna (Modern American Journals, 2025)
This article examines the syntactic structure of complex sentences in the Russian and Uzbek languages from a comparative perspective. Complex sentences, as a key syntactic unit in any language, demonstrate significant variation in their structure, conjunction types, and semantic relationships between clauses. The study focuses on the typological features of sentence formation, the use of coordinating and subordinating conjunctions, and the syntactic functions of subordinate clauses in both languages. The research identifies both universal and language-specific characteristics, reflecting the influence of grammatical categories such as word order, agglutination, and inflection. The analysis also highlights the cognitive and communicative functions of complex sentences in expressing cause-effect, conditionality, temporality, and contrast. By comparing the syntactic rules and patterns of Russian and Uzbek, this paper contributes to understanding bilingual language acquisition, translation studies, and the challenges of interlingual syntactic equivalence. The findings are particularly relevant for language teachers, translators, and researchers working in the field of contrastive grammar and syntax.
Keywords: Complex sentence, syntax, Russian language, Uzbek language, comparative grammar, conjunctions, subordinate clause, sentence structure, typology, interlingual analysis